THE ROLE OF COMPETITIONS IN THE DEVELOPMENT OF MAQOM ART - Pirmatova Nodira Yigitaliyevna; Burieva Komilakhon Rasulovna; Shamurotova Mohichehra Abdinabiyevna (Journal Park Publishing, 2024)
This article is a summary of the brief history, current status and development of the contests in Uzbekistan, which are considered important for the development of the art of maqom music, which has gained incomparable importance in the art of Uzbek classical music. It mainly talks about the competition of Maqom performers named after Yunus Rajabi in detail.